AUGMENTED REALITY-BASED LEARNING MEDIA IN INCREASING STUDENT KNOWLEDGE - Liana, Dina (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
This research aimed to find out how to apply augmented reality learning media in increasing students' knowledge at SDN 007. This research used mixed methods, namely qualitative and quantitative methods with a type of classroom action research carried out in 2 cycles with the stages of planning, implementation, observation and reflection. The research results were obtained through collecting observation data to find out the application of augmented reality-based learning media which was tested using a percentage formula and tests used to increase students' knowledge which were tested using a percentage formula. The research results obtained after applying augmented reality were that in the pre-cycle the score was 60.1%, in the 1st cycle 80.5%, and in the 2nd cycle 90%. These scores showed that after students used augmented reality learning media, students' knowledge experienced a significant increase at State Elementary School 007 Kotabaru Reteh. The benefit of applying augmented reality learning media in schools is that it can visualize abstract learning material into concrete.